Determinants factors of biotechnology commercialization in Malaysia: resource-based view perspective / Nur Hidayat Nordin - Nordin, Nur Hidayat (2023)
Managing a firmly established biotechnology company in Malaysia is challenging and requires various resources and comprehensive capabilities. With tight resources and a challenging environment, biotechnology commercialization performance has now become the main agenda to strive for in the bio-economy. Thus, this present study bridges this gap by investigating the prominent resources crucial to Malaysian biotechnology companies that may play a central role in commercialization success. In particular, this study adopts the Resource-Based View (RBV) as a grounded theory to identify enabling factors comprising the four categories: human, technological, financial, and organizational resources. An administrated survey was distributed to a total of 225 Malaysian biotechnology companies with specific criteria; companies that involve in the commercialization of biotechnology-related inventions, technology, or product. A simple random sampling approach was implemented, and data was collected via an online survey and phone interview from September 2017 until January 2018. For analysis, partial least squares path modeling (PLS-PM) software was utilized in this study. A structure path modeling has been designed based on these constructs by relating it to commercialization success using the PLS algorithm and bootstrapping method. A quantitative survey indicated that biotechnology companies indispensable a resource-based view regarding technological capability, funding access, and new talent. This study benefits the literature in commercialization study by extending the understanding of biotechnology companies’ resources and capabilities that are significant towards commercialization success. In addition, this study shed light on Malaysian biotechnology companies to develop a successful long-term business plan by concentrating on their competitive strategy, resources, and capability, thus leading to commercialization achievement.